1975
DOI: 10.3109/10826087509027336
|View full text |Cite
|
Sign up to set email alerts
|

Some Correlates of Drug Use among High School Youth in a Midwestern Rural Community

Abstract: A study of the correlates of drug use (marijuana, LSD, mescaline, speed) among high school youth in a rural, Midwestern community indicated that peer group factors were the most influential in such behavior. Also, youth from less intact families and whose parents were perceived to use various legal drugs were more prone to drug use. Drug education was seen as not having as significant an impact in differentiating between users and nonusers nor in deterring users from further involvement. In support of previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
3

Year Published

1983
1983
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(13 citation statements)
references
References 8 publications
1
9
0
3
Order By: Relevance
“…As the cost of opium is high, its affordability and the income of individual users were also important factors related to its use. An association between substance use and occupation and income has also been reported by others [10-12,25,33-35]. …”
Section: Discussionsupporting
confidence: 75%
“…As the cost of opium is high, its affordability and the income of individual users were also important factors related to its use. An association between substance use and occupation and income has also been reported by others [10-12,25,33-35]. …”
Section: Discussionsupporting
confidence: 75%
“…Parental Relationships: Numerous studies have shown that interpersonal relationships of parents to each other and to their children affect illegal drug use (Forslund, 1977-78;Johnson, et al, 1972;Kandel, ~al., 1976; National Commission on Marijuana and Drug Abuse, 1972 andStreit and Oliver, 1972;Tolone and Dermott, 1975). It is argued that an unstable homelife will increase the probability the individual will become a drug abuser.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study friends were the most common offerers, as shown in some previous studies (Tolone and Dermott 1975, Murty 1979, Pruitt et al 1991, Cousineau et al 1993, Hect and Driscoll 1994, Ghanizadeh, 2001, and the offers primarily took place at parties (Ghanizadeh 2001). The most common resistance strategies were saying 'No' (36.7%) and 'I dislike that drug' (30.5%).…”
Section: Discussionmentioning
confidence: 66%